Proceedings of the Sixth International Conference on Information and Communications Technologies and Development: Notes - Volum 2013
DOI: 10.1145/2517899.2517924
|View full text |Cite
|
Sign up to set email alerts
|

Voice-based marketing for agricultural products

Abstract: We present a study conducted in rural Northern Ghana about issues around the marketing of agricultural products and the need of mobile-based ICT solutions. The need for the spread of information and web access to communities in developing countries has given rise to the design and development of numerous ICT solutions, many of which have focused on the recent increase of mobile usage in developing countries. The contributions of this paper are: 1) Empirical results from a field survey run in Northern Ghana, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
3
10
0
Order By: Relevance
“…In addition, all end-users owned or had access to a mobile phone (Ghana has a mobile penetration of 130.9%, [12] owing to the fact that a sizable number of people have more that one phone or use multiple sims on one phone). Other research has found very little to no use of SMS and little to no use of smartphones in the rural areas of northern Ghana [6]. These findings have been further verified during this study.…”
Section: Use-case and Requirement Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, all end-users owned or had access to a mobile phone (Ghana has a mobile penetration of 130.9%, [12] owing to the fact that a sizable number of people have more that one phone or use multiple sims on one phone). Other research has found very little to no use of SMS and little to no use of smartphones in the rural areas of northern Ghana [6]. These findings have been further verified during this study.…”
Section: Use-case and Requirement Analysissupporting
confidence: 88%
“…Ghana has a literacy rate of 76.67% 1 . However, the rural north, which happens to be a major food source for the country, has its literacy rate lower than 30% 2 [6]. Currently 80 percent of online content is available in only 10 languages, which only around 3 billion people speak as their first language [7].…”
Section: Introduction 1digital Dividementioning
confidence: 99%
“…As shown in figure 1, around 25 (44%) of the reviewed papers fall in this category. Specifically, the following list of papers': (Amariles et al, 2007;Baro & Endouware, 2013;Bello-bravo & Baoua, 2012;Cáceres & Fernández-Ardèvol, 2012;Cloete & Doens, 2008;Dearden et al, 2011;Dearden et al, 2010;Dissanayeke & Wanigasundera, 2014;Dittoh et al, 2013;Lwoga, 2010;Futterman & Shuman, 2010;Gollakota et al, 2012;Kameswari et al, 2011;Kuriyan et al, 2006;Madon et al, 2009;Martin & Abbott, 2011;Mpazanje et al, 2013;Muthiah et al, 2013;Srinivasan, 2007;Patel et al, 2012;Siyao, 2012;Tomitsch et al, 2010;Mtega & Msungu, 2013;Yusop et al, 2013), main study areas focus on understanding context and documenting best practices. For instance, over five months field pilot of a voice telephony-based information service, (Futterman & Shuman, 2010) and (Yusop et al, 2013) assess the information needs and interests of rural populations in Uganda and Malaysia respectively.…”
Section: S O U R C Ementioning
confidence: 99%
“…The issue of literacy remains a barrier to the delivery of information in the current WWW formats. Ghana has a literacy rate of 76.67%, however the rural north, which happens to be a major food source for the country, retains the lowest literacy rates [6]. In addition to the above, there is an unavailability of information relevant to the livelihood of many in rural areas [3].…”
Section: Introductionmentioning
confidence: 99%